DEEP RELAXATION TECHNIQUES TO REDUCE MIDDLE-LEVEL ANXIETY IN THE FIRST GESTATIONAL MOTHER IN THE TAKING-IN PHASE - Faiqotul Amalia; Hidayah, Ridhoyanti (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: The postpartum period begins when the placenta is born and ends when the uterus returns to its normal state. During the postpartum period, physiological and psychological adaptations occur in the mother. One of the psychological conditions that can appear in postpartum mothers is anxiety. The process of pregnancy, childbirth, and the puerperium may cause anxiety, especially in primiparous mothers. Anxiety not treated immediately can lead to postpartum depression or baby blues syndrome. Objective: This research aims to apply nursing care, including assessment, diagnosis, intervention based on evidence-based practice, implementation, and evaluation of nursing Methods: The research method used interviews with patients and families and nurses' direct observations in the Visual Analog Scale for Anxiety (VAS-A) to measure anxiety levels. This research design was a case study with primiparous postpartum mothers who were given nursing intervention. Results: The patient experienced nursing problems of moderate level of anxiety, postpartum pain, knowledge deficit, and risk of infection. The primary intervention given to the patient is to provide non-pharmacological therapy using deep breathing relaxation techniques to reduce the patient's level of anxiety. Conclusion: Based on the results of nursing interventions given, it is explained that there is a decrease in the level of anxiety in patients. Thus, the patient's treatment plan was stopped and continued with self-care at home according to the recommendations given.